Enhanced energy storage performance of advanced hybrid supercapacitors derived from ultrafine Ni–P@Ni nanotubes with novel three-dimensional porous network synthesized via reaction temperatures regulation. (20th January 2020) - Li, Wei; Wu, Ming; Shi, Peng; Li, Tingting; Yue, Hongwei; Dong, Zhenwei; Gao, Yuanhao; Lou, Xiaojie
Abstract: Nickel-phosphorus semimetallic compounds with an open-framework structure have attracted increasing interests as electrode materials for supercapacitor applications. In this work, ultrafine Ni–P@Ni nanotubes (NTs) with a novel three-dimensional network are synthesized by using a one-pot hydrothermal method under different temperatures to form the electrode material for hybrid supercapacitors. The energy storage performances of the Ni–P@Ni NTs electrodes are systematically investigated, and the results demonstrate that the Ni–P@Ni NTs possess a superior specific capacity of 771.8 C g −1 at 1 A g −1 in a three-electrode cell. Remarkably, a specific capacity of 350.2 C g −1 can still be maintained when the current density increases up to 30 A g −1 . The energy storage performance of the as-prepared Ni–P nanowires (NWs) and Ni11 (HPO3 )8 (OH)6 @Ni nanoparticles (NPs) also are evaluated for comparison. Furthermore, a hybrid supercapacitor (HSC) is assembled with the Ni–P@Ni NTs as the positive electrode and activated carbon (AC) as the negative electrode. The as-assembled HSCs show a high energy density of 58.7 Wh kg −1 at a relatively high-power density of 945 W kg −1, outweighing most of the hybrid supercapacitors reported in the literature. Furthermore, such a hybrid supercapacitor displays an excellent cycling stability (91.2% after 6000 cycles at 5 A g −1 ) under a voltage of 1.6 V. Highlights: The first report on the Ni–P@Ni NTs with a 3D porous network by a facile hydrothermal method and calcination. The loaded mass of the Ni–P@Ni NTs electrode is around 8 mg cm −2, comparable with the commercial supercapacitors. The as-fabricated Ni–P@Ni NTs//AC device shows a energy density of 58.7 Wh kg −1 at a power density of 945 W kg −1 .